Faktor-Faktor yang mempengaruhi Nilai Perusahaan LQ45 di Indonesia - Ahmad Fareed Idral, Haikal Ahmad Fareed; Kusumadewi, Amalia; Margaretha Leon, Farah Margaretha (Jurnal Ekonomi Akuntansi dan Manajemen, 2025)
This study aims to identify the factors that affect firm value of companies listed in the LQ45 group of companies in Indonesia by focusing on the effect of dividend yield, debt capital, tangible assets, and free cash flow on firm value interpreted using the Tobin's Q ratio. The method used is panel data regression through the Random Effect Model (REM) approach.  The data applied in the following study originated from companies registered on the Indonesia Stock Exchange (www.idx.co.id) for five periods from 2019-2023 with a population of 70 LQ45 companies. The sample consists of 23 companies with a total of 115 observations. The results confirm that dividend yield and debt capital have a significant positive effect on firm value, while asset tangibility have a significant negative effect. Free cash flow and the interaction between dividend yield and debt capital have no significant effect. The implications of these findings suggest that managers need to maintain consistent dividend payments and an optimal debt structure, as well as ensure the efficient use of assets. For investors, focusing on dividend stability, healthy capital structure, and asset efficiency are important considerations in making investment decisions. Keywords:  Asset Tangibility, Debt Capital, Dividend Yield, Firm Value, Free Cash Flow, Tobin’s Q